The representation of social concept in Coca-Cola advertisement - Amelia, Alma Dwi; Suyatman, Ujang; Sulaeman, Dedi (Journal of Research on English and Language Learning (J-REaLL), 2024)
The aim of this research is to understand how Coca-Cola advertisements construct representations of social concepts in Coca-Cola advertisements. This research utilized qualitative methods to describe data analysis. The results of the first research showed that the Coca-Cola advertising sign contains a social concept in every advertisement displayed in advertisements on YouTube. Coca-Cola advertisements often show many people involved in them, such as interactions, relationships and dynamics between individuals or groups in society which have positive values, so that social value concepts appear in them, namely social communication, togetherness, tolerance and also concern for the environment. In the first study, researchers used the semiotic theory triangle based on Charles Sanders Peirce to describe social concepts in Coca-Cola YouTube advertisements. The author uses semiotic theory based on Charles Sanders Peirce. This theory aims to determine the relationship between representation, objects and interpretants in Coca-Cola. Furthermore, the results of the research by the two researchers found the value of the social concept in Coca-Cola's YouTube advertisement, which shows the value of social communication, togetherness, tolerance, and also concern for the environment. In addition, the researcher explains the values found, so this research is: The social signs of the concepts displayed in Coca-Cola advertisements certainly have social values that we can encounter in everyday life.